Artificial Intelligence - Eldon E. Fredericks (Journal of Applied Communications, 1986)
When Don Breneman called me last January to participate on the " New Technologies" panel, I eagerly accepted. I have a habit of eagerly accepting responsibilities that are half a year away. In June, responsibilities accepted in January have a way of causing perspiration and I don't believe that has anything to do with the weather in Fargo.